(untitled) (Global Journal of Human-Social Science, 2015)
In the present, phenomenon of information technology has been able to pass geography borders in different extends and affect on all aspects of the social, economic, military and education. so that the most remote parts of the world injoy the human beings and 21st century named century of information explosion In Iran as well as many developing countries pay attention to study in this field. the present written study the status of Information Technology in rural areas based on existing capacities in the region to enterprise facilities and capabilities and use of Management Information Systems in social services.